2021
DOI: 10.1161/atvbaha.120.315081
|View full text |Cite
|
Sign up to set email alerts
|

Xanthine Oxidase Drives Hemolysis and Vascular Malfunction in Sickle Cell Disease

Abstract: Objective: Chronic hemolysis is a hallmark of sickle cell disease (SCD) and a driver of vasculopathy; however, the mechanisms contributing to hemolysis remain incompletely understood. Although XO (xanthine oxidase) activity has been shown to be elevated in SCD, its role remains unknown. XO binds endothelium and generates oxidants as a byproduct of hypoxanthine and xanthine catabolism. We hypothesized that XO inhibition decreases oxidant production leading to less hemolysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…Cellular production of H 2 O 2 was evaluated by its fluorescent reaction product with coumarin boronic acid (Cayman, 14051) in the presence of l -NAME (Cayman, 80210) and taurine (Cayman, 27031) [ [31] , [32] , [33] ]. Coumarin boronic acid (CBA) is a sensitive probe for hydrogen peroxide, but necessary control must be included to rule out interference from peroxynitrite and hypochlorous acid.…”
Section: Methodsmentioning
confidence: 99%
“…Cellular production of H 2 O 2 was evaluated by its fluorescent reaction product with coumarin boronic acid (Cayman, 14051) in the presence of l -NAME (Cayman, 80210) and taurine (Cayman, 27031) [ [31] , [32] , [33] ]. Coumarin boronic acid (CBA) is a sensitive probe for hydrogen peroxide, but necessary control must be included to rule out interference from peroxynitrite and hypochlorous acid.…”
Section: Methodsmentioning
confidence: 99%
“…Transfected hPMVECs were tryspinized and then resuspended in Mg 2 and Ca 2+ free Hank's Balanced Salt Solution (HBSS). In a 96 well plate 150 000 cells and 5 μM MitoSOX Red™ (Invitrogen) were added.…”
Section: Methodsmentioning
confidence: 99%
“…Sickle cell disease (SCD) is an inherited hemoglobinopathy that results in sickling of deoxygenated red blood cells (RBC) due to a point mutation in the beta-globin gene. 1 In SCD, there is an increase in oxidative stress due to augmented reactive oxygen species (ROS) production from enzymatic sources such as xanthine oxidase 2 and non-enzymatic sources including Fenton chemistry. 3 Paired with this increase in ROS production is a compromised antioxidant system.…”
Section: Introductionmentioning
confidence: 99%
“…A study of febuxostat also did not demonstrate an overall benefit to patients with stage three kidney disease, but did show a benefit in patients without proteinuria or better initial kidney function at baseline. 6 Murine SCA models have demonstrated that hyperuricemia is associated with hemolysis and treatment with febuxostat improved the hemolytic phenotype.. 7 This association between uric acid and change and eGFR in SCA will need to be confirmed in a prospective randomized controlled trial of uric acid lowering medication.…”
Section: Hyperuricemia and Abnormal Nocturnal Dipping Impact Glomerul...mentioning
confidence: 99%
“…We utilized the clinical documentation and radiological reports/images to assess the ORR based on the criteria described previously in prospective and retrospective adult histiocytosis studies. [7][8][9][10][11] We captured the best response, either clinical or radiological, depending on the organ involvement. Among patients with isolated skin involvement, response assessment was based on clinical examination.…”
Section: Hyperuricemia and Abnormal Nocturnal Dipping Impact Glomerul...mentioning
confidence: 99%